Ear, nose and throat foreign bodies and their spectrum in rural South India - Rai, S. Juthika; Chandre Gowda, B. V.; Kamath, Rakshita R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Ear, nose and throat foreign bodies are among the most common emergencies presenting to Otorhinolaryngologists world over and when dealt with poorly can cause high morbidity and mortality. Our study aimed at analysis of age, gender, types of foreign bodies and various aspects of their management in rural population. Methods: An observational prospective study was conducted in MVJ Medical College and Research hospital, Hoskote which is a tertiary care teaching hospital in rural Karnataka. 224 patients complaining of foreign body in ear, nose and throat between June 2018 to December 2019 were analyzed. Results: Among 224 patients, majority were >10 years of age (57%). Most common site was ear (63.8%) followed by nose and throat. Single site foreign bodies were vast with cotton being most common object. About 67% foreign bodies were organic objects with 28%living and 72% non-living. 4% of the cases needed anesthetic augmentation for removal of which only 8 cases required general anesthesia. 60% cases were previously attempted removal cases with 2.7% cases developing sequela at follow up. Conclusions: Early presentation, timely intervention and skilled removal by otorhinolaryngologists can help prevent adverse outcomes of foreign body Ear Nose and throat.